The Influence of Village Fund Allocation on Economic Growth in South Sumatra Province 2016–2023 - Prasojo, Mukti; Utomo, Yuni Prihadi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of Village Fund Allocation (ADD) on economic growth in 13 regencies of South Sumatra Province from 2016 to 2023. Using panel data regression analysis with the Common Effect Model (CEM) as the best estimated model, the research also examines the impact of other variables including the Human Development Index (HDI), Regional Budget (APBD), Construction Cost Index (IKK), number of community health centers (HEALTH), and labor force (EMP). The empirical findings reveal that ADD and HDI have a statistically significant influence on regional economic growth, with ADD demonstrating a negative effect, while HDI exerts a positive influence. In contrast, APBD, IKK, HEALTH, and EMP show no significant relationship with economic growth. The results suggest that while human capital development plays a critical role in promoting sustainable economic progress, the effectiveness of fiscal policies such as ADD and APBD depends heavily on governance quality and institutional capacity. The study highlights the need for institutional reform, transparent fund management, and a development strategy tailored to local potential to ensure inclusive and productive regional economic growth.